PENGARUH KEGIATAN EKSTRAKURIKULER PRAMUKA TERHADAP KEDISIPLINAN PESERTA DIDIK DI SDN 06 JAMBU DESA BERINGIN KECAMATAN SAJAD - Muhammad Wildani; Parni Parni (Cross-border, 2018)
The purpose of this research is to reveal about: 1) scout extracurricular activities at 06 Jambu school year 2019-2020. 2) discipline of students in 06 Jambu school year 2019-2020. 3) influence of scout extracurricular activities towards discipline of students in 06 Jambu school year 2019-2020. This study uses a quantitative approach and type of associative research. Data collection techniques using direct communication techniques, indirect communication techniques, and documentation. The data analysis technique used is descriptive statistics, Pearson product moment correlation, linear regression. The results showed that: Scout extracurricular activities are classified as "adequate", namely 68.3%. These categories can be broken down by the following indicators: religious programs, professional training, student organizations, cultural / cultural activities and camp programs. Student Discipline is classified as "Good", which is equal to 100%. These categories can be specified with the following indicators: discipline in learning, attitude discipline, and time discipline. Scout extracurricular activities do not have a significant effect on the Discipline of Students at SDN 06 Jambu for the 2019/2020 academic year. Because, the probability value of 0.05 is smaller than the significant probability value of 0.990 or 0.05 <0.990 with a determinant coefficient value of 0.00%, the remaining 100% is influenced by other factors outside the research problem with the regression equation Y '= 88.288 - 0.002X.